IMPROVING THE EFFECTIVENESS OF REGIONAL ASSETS MANAGEMENT: INTERACTION BETWEEN AUDIT FINDINGS, FOLLOW-UP ON AUDIT RESULTS, AND HUMAN RESOURCE COMPETENCE IN MEDAN CITY - Selly Yunita; Irfan (PT. Radja Intercontinental Publishing, 2026)
Regional Asset Management (BMD) is a crucial pillar for public accountability, yet its effectiveness is often hampered by recurring audit findings and symbolic compliance practices. This study aims to analyze the interaction between audit findings, audit follow-up actions (TLHP), and human resource (HR) competency in improving the effectiveness of the BMD management system in the Medan City Government. Using a descriptive qualitative approach assisted by NVivo 14 data analysis software , data were collected through in-depth interviews with asset practitioners, Focus Group Discussions (FGDs), and document analysis of the Audit Result Reports (LHP) of the Indonesian Supreme Audit Agency (BPK RI) for the 2020-2024 period. The results show that audit findings function as coercive institutional pressure, but the system's effectiveness substantially depends on the quality of the TLHP, which is strongly moderated by HR competency. These findings reveal a decoupling phenomenon , where low competency and high employee turnover lead to merely administrative asset improvements in pursuit of an Unqualified Opinion (WTP). Conversely, competent and stable HR acts as a transformational bridge that transforms auditor recommendations into tangible and permanent asset governance improvements. This study makes a theoretical contribution to Institutional Theory by emphasizing the role of internal absorptive capacity in determining the success of policy integration in the public sector. The study's limitation lies in its single focus on the Medan City area, so it is recommended for future research to adopt mixed - methods with a broader geographic scope to test the generalizability of the proposed variable interaction model. Regional Asset Management (BMD) is a crucial pillar for public accountability, yet its effectiveness is often hampered by recurring audit findings and symbolic compliance practices. This study aims to analyze the interaction between audit findings, audit follow-up actions (TLHP), and human resource (HR) competency in improving the effectiveness of the BMD management system in the Medan City Government. Using a descriptive qualitative approach assisted by NVivo 14 data analysis software , data were collected through in-depth interviews with asset practitioners, Focus Group Discussions (FGDs), and document analysis of the Audit Result Reports (LHP) of the Indonesian Supreme Audit Agency (BPK RI) for the 2020-2024 period. The results show that audit findings function as coercive institutional pressure, but the system's effectiveness substantially depends on the quality of the TLHP, which is strongly moderated by HR competency. These findings reveal a decoupling phenomenon , where low competency and high employee turnover lead to merely administrative asset improvements in pursuit of an Unqualified Opinion (WTP). Conversely, competent and stable HR acts as a transformational bridge that transforms auditor recommendations into tangible and permanent asset governance improvements. This study makes a theoretical contribution to Institutional Theory by emphasizing the role of internal absorptive capacity in determining the success of policy integration in the public sector. The study's limitation lies in its single focus on the Medan City area, so it is recommended for future research to adopt mixed - methods with a broader geographic scope to test the generalizability of the proposed variable interaction model.